Optimization of Coffee Farmers in Modern and Traditional Coffee Processing to Increase Selling Price in Lemah Putih Village - Tri Putra Olasari; Achmad Otong Bustomi; Edy Setyawan (Faculty of Islamic Economics and Business IAIN Syekh Nurjati Cirebon, 2023)
Coffee, beloved for its complex flavor and invigorating aroma, is brewed from roasted and ground coffee beans. Quality beans processed using optimal methods can significantly increase the selling price of Indonesian coffee, both domestically and internationally. Within the context of economics, particularly in free market systems, the market plays a critical role. It functions as the mediator between producers, who offer goods, and consumers, who determine demand through their purchasing choices. In this dynamic, consumers hold significant power, dictating the flow of goods and services through their preferences.However, there are challenges faced by coffee farmers in Lemahputih Village. This study aims to address these challenges by focusing on three key questions(1)Optimization Strategies: How can coffee farmers in Lemahputih Village optimize their operations for both modern and traditional coffee processing methods?. (2) Quality and Price: How can improved processing techniques enhance the quality of coffee produced in Lemahputih Village, thereby increasing its selling price? (3) Islamic Economics Perspective: In the context of Islamic economics, what approaches can be employed to further increase the selling price of coffee produced in Lemahputih Village?This study addresses a gap in previous research by delving deeper into the theoretical perspectives surrounding coffee processing and optimization within the framework of Islamic economics.Research Methods:This study employs a descriptive research approach, aiming to capture and analyze factual information concerning the optimization of coffee processing methods in Lemahputih Village. This qualitative method, also known as the analytical method, involves data collection through various means, including interviews with coffee farmers, village officials, and relevant market stakeholders. Additionally, the study draws upon existing statistical data and relevant literature to provide a comprehensive analysis of the current situation and potential optimization strategies.